François Truffaut e Arthur Schopenhauer: além do amor e da paixão - Góes, Véra Lúcia de (2021)
François Truffaut was a great film critic, with many works published in Cahiers du Cinéma, a French magazine launched in the 1940s and still in operation. After his experience as a critic, he became a filmmaker, sharing ideas with Jean-Luc Godard and others, who, in the 60s and 70s, led the French movement later known as Nouvelle Vague. Truffaut is publicly recognizes as having a keen interest in romantic relationships. The basic themes of all his films were love, women and temporality. Arthur Schopenhauer, 19th century philosopher, author of Metaphysics of Love – Metaphysics of Death, who expresses the description of love between the sexes and their consequences. This thesis shows that Truffaut’s gaze went beyond love and passion, reaching an almost unhealthy obsession with the speed of time, and how his films relate to the philosopher’s theory.